Química a microescala en la enseñanza experimental usando una microbalanza de cristal de cuarzo - Gonzales-Balladares, Julio David (2022)
This study proposes a laboratory practice at the university level that allows active participation and helps understand the concepts of physical-chemical properties and molecular structures with experimentation as a teaching-learning strategy for microscale chemistry. For it, a quartz crystal microbalance is used to detect variations of small amounts of mass. The microbalance is built with low-cost electronic components, an Arduino UNO board, and an OLED screen to determine the evaporation time at room temperature of pure substances and mixtures with different degrees of volatility: Propan-2-ol, ethanol, and water. And with its use, reduce the cost of the chemical reagents used, the amount of waste generated, and reduce the time in the experiments to allow greater participation in the debate and discussion between students and teachers during practice.